Penambahan Astaxanthin pada Pengencer Kuning Telur Berbagai Jenis Unggas Dapat Memproteksi Semen Babi Selama Penyimpanan (THE ADDITION OF ASTAXANTHIN ON SPERM DILUENTS PHOSPHATE EGGYOLK OF VARIOUS POULTRY CAN PROTECT QUALITY OF PIG SPERM DURING STORAGE) - Bebas, Wayan; Gorda, Wayan (Jurnal Veteriner; Vol 17 No 4 (2016), 2017)
A study was conducted to formulate semen diluent of pigswith a better quality, cheap and easy toprepare using egg yolk of various poultries such as chickens, ducks and quails in combinationwithastaxanthin, a potent antioxidant. The research design used was a completely randomized factorialdesign with three different types of sperm diluents and four levels of astaxanthin concentration. Spermdiluents used were phosphate duck egg yolk, phosphate quail egg yolk and yolks phosphate supplementedrespectivelywith 0,002%, 0,004% and 0,008%astaxanthine. The treated sperm were strored at 5oC for 48hours. The sperm qualities were examined for progressive motility, spermatozoa abnormalities, viabilityand plasma membrane integrity. The result showed that sperm diluents of using duck egg yolk phosphatein combination with 0.002% astaxanthinresulted in the highest progressive motility, viability and plasmamembrane intact while abnormalities spermatozoa is lowest. It can be concluded that phosphate duck eggyolk sperm diluents with the addition of 0,002% astaxanthinappeared to be able to maintain the qualityof pig sperm stored at 5oC for 48 hours.
Keywords: sperm diluents; egg yolk of various poultry; astaxanthin; pig semen quality